The study on current of upward aborted leader initiated from Zi-Feng tower. (November 2018) - Luo, Xiaojun; Zhang, Qi; Fu, Yapeng; Yang, Bo; Guo, Fei; Duan, Yantao
Abstract: In this study, the characteristics analysis on current of three sets of upward aborted leaders initiated from Zi-Feng tower in response to nearby lightning is performed. All of them had only an initial stage, not followed by any return-stroke sequences. With duration time of 83.3μs–590.6 μs, the measured current train is composed of a series of pulses. The pulses are close to a double exponential wave with the pulse width of about 7.7 μs ∼18.7 μs, and the rising time is on the order of sub-microseconds. The time interval between the neighboring pulses is about 18.6 μs The peak of pulse current ranges from 1.6 A to 226 A. With respect to the transferred charge of pulse, it ranges from 19 μC to 195.3 μC. Moreover, the possible reason for how the upward aborted leader starts is discussed. The presented statistical results may be of assistance in understanding initial continuous current and the initiation of upward leader at tall grounded objects, as well as in building more appropriate protective measures against lightning hazards. Highlights: Current characteristics of three sets of upward aborted leaders are analyzed. The peak of pulse current ranges from 1.6 A to 226 A. The transferred charge of pulse current ranges from 19 μC to 195.3 μC. Possible reason for how the upward aborted leader starts is discussed.